FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA ESG DI NEGARA BERKEMBANG: TINJAUAN LITERATUR - Adli Rikanda Saputra (CV. Denasya Smart Publisher, 2026)
This study reviews the determinants of Environmental, Social, and Governance (ESG) performance in developing countries. ESG has become an important framework for assessing corporate sustainability, yet its implementation in developing countries remains constrained by weak institutional quality, limited regulation, low stakeholder pressure, and inadequate ESG data availability. This study applies a literature review approach by synthesizing 60 scholarly articles published between 2019 and 2026 on ESG performance, ESG disclosure, and ESG determinants in emerging markets. The review shows that ESG in developing countries is influenced by both internal and external determinants. Internal determinants include firm size, profitability, leverage, ownership structure, board characteristics, management characteristics, innovation, and R&D investment. External determinants include institutional quality, ESG regulation, financial market development, stakeholder pressure, national culture, political stability, environmental vulnerability, and international integration. The findings also indicate that ESG determinants vary across environmental, social, and governance dimensions as well as across industrial sectors. This review concludes that ESG development in developing countries is highly contextual and cannot be fully explained using frameworks derived from developed economies. Future studies should employ longitudinal, comparative, and context-sensitive designs, extend analysis to SMEs and underexplored sectors, improve ESG measurement, and examine how ESG contributes to sustainable development in developing economies.